Fatigue Strength Analysis of Reducer Brake Caliper of Enhanced Car T·JK4 - 郭富强; 吴丹; 商跃进; 王红 (机车电传动)
This paper has calculated and analyzed the load condition of reducer brake caliper of enhanced car T.JK4. The static strength of brake caliper has been analyzed by using finite element analysis. The fatigue strength has been analyzed by the method provided by ORE B12/RP17 research report and the fatigue strength of brake caliper has also been tested. The results show that the test results and analysis results are basically the same and both the fatigue strength and fatigue life are meeting the requirements of relevant standards.